Differenzialtherapie von Kopfschmerzen - Diener, Hans Christoph; Holle-Lee, Dagny; Nägel, Steffen; Gaul, Charly (DMW - Deutsche Medizinische Wochenschrift, 2017)
A precondition for the successful treatment of headaches is the correct headache diagnosis. Triptans are effective for attack treatment of migraine and cluster headache. However, there are not effective for the treatment of tension-type headache. For the prevention of frequent episodic migraine betablockers, flunarizine, topiramate and amitriptyline are recommended. For the prevention of chronic migraine evidence is only available for onabotulinumtoxinA and topiramate. For prophylactic treatment of tension-type headaches tricyclic antidepressants are used. In cluster headache verapamil (in combination with steroids) is the most frequently used prophylactic agent. This article focusses on the current acute and prophylactic treatment of common headache syndromes.
Keywords: Migräne; Kopfschmerz vom Spannungstyp; Trigeminoautonome Kopfschmerzen; Cluster Kopfschmerz